농업경제학에서 거래비용경제학의 유용성 - 권오복 (한국농촌경제연구원, 2004)
Abstract Various types of agricultural organizations and institutions have appeared due to severe competition in agricultural markets and changes in consumers' preference for food. Production and marketing contracts , producers' organizations, and collective sales by producers may be good examples. The basic role of agricultural economics is to explain how such things works. In this context, a brief structure of the Transaction Cost Economics (TCE) is reviewed and the potential contributions of the TCE to agricultural economic research is suggested. Although there are some empirical research limitations, the paper argues, TCE would be a good tool for analyzing agricultural contract, agricultural cooperatives and producers' organizations, vertical integration, standardization and grading system of agricultural products, and agribusiness.
Keywords: 거래비용경제학; 거래비용; 자산특수성; 거래빈도; 농업경제학; Transaction Cost Economics; Transaction Costs; Asset Specificity; Frequency of Transaction; Agricultural Economics